Inspirations of the religious worldview for sustainable development - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2016)
The global community today is extremely concerned with the accelerating deterioration of the natural environment and its destructive consequences on human and life on earth. ‘Sustainability’ is the key idea to deal with many of critical questions posted by ecological crisis. Among many others, Man’s attitudes toward nature and his methods of interacting with the natural world have been identified as root causes of environment problems. It is undeniable that the accelerating growth of human population on earth puts more pressure on natural resources to satisfy the increasing needs of mankind, but the green technologies that guided by moral values should be capable of tackling this major problem. Man’s attitudes toward nature are determined by his worldview which emanates from a religion or culture; while his methods of interaction with nature are determined by advancement in science and technology. These two modes of factors, i.e. religious and scientific, will identify the root causes of environment crisis with regard to Man’s activities on earth. The major objective of this article is to investigate how religious worldview may contribute in developing strategies for sustainable development, especially Development Plans of United Nation for the entire global community. Using built environment as unit of analysis, the article exposes the religious wisdom to the theory of sustainable development. It emphasizes that the power of science and religious wisdom must be integrated for better management of both the natural environment and development of human community. The article concludes that the religious worldview can play a crucial role to change man’s view, his method of interaction with nature, and emphasizes protection of the natural environment from destructive activities of mankind.